Stretch too far: rectus sheath haematoma secondary to repetitive trauma and increased intra-abdominal pressure. Issue 1 (19th January 2021) - Reider, Joshua; Radtke, Logan; Heiberger, Caleb Joseph; Yim, Douglas
Abstract : A 26-year-old man presented with a 4-week history of right lower quadrant abdominal pain which was managed conservatively at home with ibuprofen. Three days later, he presented to the emergency department with worsening pain and swelling following an episode of coughing and slipping in the bathroom. Following his admission, CT angiography showed an active bleed into a 4.6×6.7×11 cm right rectus sheath haematoma, just inferior to the umbilicus. The patient was then referred to interventional radiology for an angiogram and coil embolisation. A superselective branch angiogram showed contrast extravasation from a medial branch of the right inferior epigastric artery, successfully embolised without incident.